Correlation analysis between the performance in individual phases with overall performance of world champion 110-meter hurdlers - Huang, Y.; Zhou, Y.H.; Wang, L.J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: By analyzing the kinematic data of 110-meter hurdlers a correlation can be found between performance in each period and overall performance. This information may be used to suggest strategies for improvement in 110-metre hurdling.